PERANCANGAN SISTEM INFORMASI KENAIKAN PANGKAT DAN GOLONGAN GURU SMKN 1 SAWAHLUNTO BERBASIS WEB - Eko Amri Jaya; Indah Febriyani; Rahmat Putra (Jurnal Sains dan Teknologi: Jurnal Keilmuan dan Aplikasi Teknologi Industri, 2022)
SMKN 1 Sawahlunto is one of the vocational high schools located in Talawi District, Sawahlunto City. The promotion system and classes that run in this school is still done manually using Microsoft excel. This causing the process of processing data to rise through the ranks is time-consuming and costly in collecting files for material requirements to be promoted. Therefore, this research was carried out with the aim of developing an application that can manage data and files for promotion and teacher classes of SMKN 1 Sawahlunto web-based. System development is carried out using use case diagrams, activity diagrams and class diagrams. The method used in this study is the waterfall method to analyze the system to be developed in order to provide convenience to each teacher in applying for promotion and class. From the results of the trials that have been carried out, it shows that the system that has been made can run effectively, efficiently and make it easier for teachers of SMKN 1 Sawahlunto to apply for promotion and class.